Effect of lithiation on the elastic moduli of carbon fibres. (15th November 2021) - Duan, Shanghong; Iyer, Anand H.S.; Carlstedt, David; Rittweger, Florian; Sharits, Andrew; Maddox, Calvin; Riemschneider, Karl-Ragmar; Mollenhauer, David; Colliander, Magnus; Liu, Fang; Asp, Leif E.
Abstract: Carbon fibre electrodes can enable a solid-state battery to carry mechanical load as normal construction materials. The multifunctionality is promising for most lightweight applications. Like all electrode materials, both volume and elastic moduli of the carbon fibre electrodes change during battery cycling. Such changes jeopardize the mechanical integrity of the battery. Due to the challenging corrosion problem of the lithiated component in air, the effect of lithiation on the carbon fibre's elastic moduli has yet to be explored. Also, robust data on the expansion of carbon fibres from lithiation are lacking. In the present work, we demonstrate a method and perform tests of corrosion protected carbon fibres in scanning electron microscope. The volume, and longitudinal and transverse moduli of a carbon fibre at three states of lithiation are determined and compared. The transverse modulus of the lithiated fibre is found to be more than double that of the pristine and delithiated fibres. Graphical abstract: Image 1 Highlights: Mechanical experiment on single lithiated carbon fibres is demonstrated. Volume expansion and elastic moduli change of a carbon fibre electrode are measured. The transverse modulus of a carbon fibre electrode is doubled after Li insertion.